2020
DOI: 10.1088/1361-6463/ab876b
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport dynamics and the effects on electrical tree degradation under DC voltages in thermally aged silicone rubber

Abstract: Electrical tree is one of the major issues for insulation failure in high voltage power cables. In this paper, we investigate electrical tree degradation under DC voltages in thermally aged silicone rubber (SIR). Charge transport dynamics are revealed by means of space charge measurement and simulation to give a better insight into the electrical tree initiation and evolution. The results show that a thermal oxygen reaction enhances the SIR cross-linked networking and thus gives rise to a higher tree initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…1.6×10 13 2.0×10 13 2.4×10 13 Trapping 1.58×10 13 2.37×10 13 9.0×10 9 1.2×10 10 1.5×10 10 Energy released by space charges (eV/m³) Detrapping 1.24×10 10 1.63×10 10 Notably, the DC and AC peak electric field strengths were the same. Compared with the DC electric field, the energy released by the space charge of trapping, detrapping, and recombination in the AC electric field was approximately twice as much as that in the DC electric field, while the RMS AC field was 30% less than that of the DC field.…”
Section: Energetic Aspects Of the Dynamic Behavior On Insulationmentioning
confidence: 96%
See 1 more Smart Citation
“…1.6×10 13 2.0×10 13 2.4×10 13 Trapping 1.58×10 13 2.37×10 13 9.0×10 9 1.2×10 10 1.5×10 10 Energy released by space charges (eV/m³) Detrapping 1.24×10 10 1.63×10 10 Notably, the DC and AC peak electric field strengths were the same. Compared with the DC electric field, the energy released by the space charge of trapping, detrapping, and recombination in the AC electric field was approximately twice as much as that in the DC electric field, while the RMS AC field was 30% less than that of the DC field.…”
Section: Energetic Aspects Of the Dynamic Behavior On Insulationmentioning
confidence: 96%
“…Polymer molecular bonds can be broken and reconstructed through energetic processes induced by the charges, representing a possible triggering step to electrical treeing. 10 Several studies have shown that the dynamic behavior of space charges is often accompanied by the release of energy. 2,11,12 Such energy exchanges, which can alter the chemical properties of polymer molecules and degrade the material, can occur near the interfaces during the injection and extraction of charges.…”
Section: Introductionmentioning
confidence: 99%
“…Gardette et al 21 revealed that elevated temperatures result in the disintegration of molecular chain of polyethylene, which leads to the formation of free radicals. Zhang et al 22 suggested that the electrical properties of aged SiR, such as electrical tree initiation voltage, show a trend of first increasing and then decreasing. Ito et al 23 found that the mechanical properties of aged SiR decrease, while the hardness and dielectric properties increase.…”
Section: Introductionmentioning
confidence: 99%
“…transportation, aerospace, electronics, and electrical systems. [1][2][3][4] However, as the development of application fields, performance requirements of different materials have increased. Further enhancing the thermal stability of silicone rubber has become an important topic.…”
Section: Introductionmentioning
confidence: 99%